Beyond Income: Dynamic Consumer Financial Vulnerability - Salisbury, Linda Court; Nenkov, Gergana Y.; Blanchard, Simon J.; Hill, Ronald Paul; Brown, Alexander L.; Martin, Kelly D. (Journal of Marketing, 2023)
This research challenges the entrenched belief that financial vulnerability affects only low-income consumers. Instead, most consumers across the socioeconomic spectrum experience varying degrees of financial vulnerability at different points during their lives, whether sporadically or chronically; vulnerability is dynamic and heterogeneous. The authors propose a novel, theory-driven definition of consumer financial vulnerability (CFV) as the risk of incurring future harm, given the consumer's current access to various financial resources. A new conceptual framework decouples “vulnerability” from “harm” to distinguish the state of CFV, its determinants (access to various interdependent financial resources), and the constructs it foreshadows (multiple interconnected forms of realized harm). Five research propositions follow: (1) financial resource volatility plays a vital role in CFV, (2) recovering from harm requires more financial resources than preventing harm, (3) a multiperiod lens is needed to assess CFV accurately, (4) greater financial resource access can increase CFV, and (5) generalized financial literacy is not a panacea for mitigating CFV. The propositions and their implications for marketing strategy, public policy, and consumer well-being offer a rich research agenda. The authors propose a measure of CFV—the probability that financial resources are insufficient to meet or exceed a harm threshold—for future empirical investigations.